Language Interpreters as Cultural Brokers in Music Therapy - Davenport, Victoria (Voices: A World Forum for Music Therapy, 2024)
In an increasingly linguistically diverse society, music therapists in the United States are working with individuals who may not speak the dominant English language (Davenport, 2024). It is important that music therapists collaborate with language interpreters when language discordance occurs, that is, when the music therapist and patient do not have a shared proficiency of the same language. There are many ways of working with interpreters, but the topic is not widely researched in the music therapy profession. In this reflection paper, I discuss the ways in which music therapists and language interpreters can collaborate, highlighting the importance of the cultural broker stance and inviting interpreters into the therapeutic space.